Towards sound and effective regulation of competition in the banking industry in Ghana to promote stability efficiency and economic growth - OluSoyeju, Olufemi Olugbemiga (University of Pretoria, 2018)
Mini Dissertation (LLM)--University of Pretoria, 2017.